RDWI is Better Discriminant than RDW in Differentiation of Iron Deficiency Anaemia and Beta Thalassaemia Trait - Nesa, Ayatun; Tayab, Md Abu; Sultana, Tuhin; Khondker, Lubna; Rahman, Md Quddusur; Karim, Md Anwarul; Ahmed, AN Nashimuddin (Bangladesh Journal of Child Health, 2010)
Iron deficiency anemia (IDA) and beta-thalassemia trait (BTT) are the common causes of microcytic hypochromic anaemia. Several discrimination indices have been introduced to discriminate quickly these similar entities via parameters obtained from automated cell counter. The purpose of the study was to compare the value of two discrimination indices, red cell distribution width index (RDWI) and red cell distribution width (RDW) in differentiation of BTT and IDA. This study consists of 57 cases of BTT and 72 cases of IDA. Severe anaemia (<7.0 gm/dl) had been excluded because these cases are not confused with BTT cases in practice. Sensitivity, specificity, positive and negative predictive values and Youden’s index of both indices in differentiation of BTT and IDA had been calculated. RDWI appears to be reliable and useful index for differentiation of iron deficiency anaemia and beta thalassaemia trait. Again RDWI is better than RDW in differentiating BTT from IDA. Key words: Microcytic hypochromic anemia; discrimination indices. DOI: 10.3329/bjch.v33i3.5690 Bangladesh Journal of Child Health 2009; Vol.33(3): 100-103